Os saberes matemáticos que constituem o aterro sanitário de resíduos sólidos da cidade de araguaína. - DAMASCENO, Elaine Cristina Medeiros Ribeiro (Universidade Federal do Tocantins, 2023)
This work aims to expose the production of solid waste, from Araguaína of the Tocantins state. Through a survey carried out with the company Litucera Cleaning and Engineering, data were obtained on the amount of garbage that is produced in Araguaína and the landfill, we will show that the city has developed, without any planning, the closure of the Araguaína dump and its transfer. Reveal that for the construction of a landfill is necessary a study of the area so they do not cause so much impact to the environment, its implementation is obligatory to obey the laws, and that the legislation is for everyone. The choice of the area was essential that there was a large investment with technological devices to implement the enterprise. To create the mathematical models and to discover the life span of a landfill and its volume the methodology to be endowed was modeling where we will expose mathematical models which will be satisfactory for the problems involved, where it will be expressed through interaction, In this situation, the volume of each cell (place to receive the trash) will be viewed, the transformation of the area into meters and how many tons will be produced by 2050 by the population of Aragua.